The position of illegal immigrants / Hasnan Hamzah - Hamzah, Hasnan (Faculty of Law, 1987)
The aim of this study is to examine and recognise the position of illegal immigrants. There are many questions which need to be answered, inter alia: What are their rights? What is their Status? Can they enjoy the same rights as the citizens of the country do? What protections do they have? Since there are no decided Malaysian case law on the subject, the writer was faced with a number of difficulties especially in defining the term "illegal immigrants" (Chapter Two) and discussing their position (Chapter Three). The present situation in Malaysia is that the law is unsettled on the definition of "illegal immigrants". There are still confusions... concerning the term "illegal immigrants" and " refugees" which further complicates the extension to them of the treatment that they deserve. The scarcity of cases, rulings of the courts and opinion of the authorities also adds weight to the problems concerning their position. Legally speaking, these immigrants are illegal since their entry is illegal and they remain as such until they take certain steps to legalise their stay here. Until that time they can be deported back to their country or to their last port of call outside of Malaysia.